Co-Amorphization of Kanamycin with Amino Acids Improves Aerosolization - Bishal Raj Adhikari; Kārlis Bērziņš; Sara J. Fraser-Miller; Keith C. Gordon; Shyamal C. Das (MDPI AG, 2020)
Different formulation techniques have been investigated to prepare highly aerosolizable dry powders to deliver a high dose of antibiotics to the lung for treating local infections. In this study, we investigated the influence of the co-amorphization of a model drug, kanamycin, with selected amino acids (valine, methionine, phenylalanine, and tryptophan) by co-spray drying on its aerosolization. The co-amorphicity was confirmed by thermal technique. The physical stability was monitored using low-frequency Raman spectroscopy coupled with principal component analysis. Except for the kanamycin-valine formulation, all the formulations offered improved fine particle fraction (FPF) with the highest FPF of 84% achieved for the kanamycin-methionine formulation. All the co-amorphous formulations were physically stable for 28 days at low relative humidity (25 °C/<15% RH) and exhibited stable aerosolization. At higher RH (53%), even though methionine transformed into its crystalline counterpart, the kanamycin-methionine formulation offered the best aerosolization stability without any decrease in FPF. While further studies are warranted to reveal the underlying mechanism, this study reports that the co-amorphization of kanamycin with amino acids, especially with methionine, has the potential to be developed as a high dose kanamycin dry powder formulation.